Design of helical-coil heat exchanger for acetone cooling - Pérez Sánchez, A.; Pérez Sánchez, E.J.; Heredia Sánchez, A.; Pazos Amayuela, L. (Nexo Revista Científica, 2019)
The helical coil heat exchangers are employed in several applications due to their compact structure and the high heat transfer coefficients usually obtained. In the present work, the design of a helical coil heat exchanger is accomplished in order to carry out the cooling of a liquid acetone stream. The equipment will has an overall heat transfer coefficient of 23.88 kcal/h.m2.ºC; a heat transfer area of 6.60 m2; an actual number of turns of coil equal to 53; and a height of 2.58 m. Both the acetone and the water stream do not exceed the maximum pressure drop established by the process. The influence of increasing both the acetone feed flowrate and inlet temperature on four design parameters of the helical coil heat exchanger: global heat transfer coefficient, heat transfer area, actual number of turns of the coil, and height of the equipment, was also determined, obtaining as a result that the increase of the two initial variables increases the values ​​to be obtained of these four parameters. Excel spreadsheets were used to obtain the graphics and to solve the design methodology used in this study.